Laser Microdissection-Based Tissue-Specific Transcriptome Analysis Reveals a Novel Regulatory Network of Genes Involved in Heat-Induced Grain Chalk in Rice Endosperm - Ishimaru, Tsutomu; Parween, Sabiha; Saito, Yuhi; Shigemitsu, Takanari; Yamakawa, Hiromoto; Nakazono, Mikio; Masumura, Takehiro; Nishizawa, Naoko K.; Kondo, Motohiko; Sreenivasulu, Nese (Oxford University Press, 2019)
Heat stress occurrence during seed filling leads to the formation of a chalky portion in the limited zone of the starchy endosperm of rice grains. In this study, isolation of aleurone, dorsal, central and lateral tissues of developing endosperm by laser-microdissection (LM) coupled with gene expression analysis of a 44 K microarray was performed to identify key regulatory genes involved in the formation of milky-white (MW) and white-back (WB) grains during heat stress. Gene regulatory network analysis classified the genes changed under heat stress into five modules. The most distinct expression pattern was observed in modules where most of the small heat shock proteins and cellular organization genes were changed under heat stress in dorsal aleurone cells and dorsal starchy endosperm zones. The histological observation supported the significant increase in cell number and size of dorsal aleurone cells in WB grains. With regard to the central starchy endosperm zone, preferential down-regulation of high molecular weight heat shock proteins (HMW HSPs), including a prominent member encoding endoplasmic reticulum (ER) chaperones, by heat stress was observed, while changes in expression of starch biosynthesis genes were minimal. Characterization of transgenic plants suppressing endosperm lumenal binding protein gene (BiP1), an ER chaperone preferentially down-regulated at the MW zone under heat stress, showed evidence of forming the chalky grains without disturbing the expression of starch biosynthesis genes. The present LM-based comprehensive expression analysis provides novel inferences that HMW HSPs play an important role in controlling redox, nitrogen and amino acid metabolism in endosperm leading to the formation of MW and WB chalky grains under heat stress